AN ESTIMATION OF QUANTITY OF THE IDENTIFIED OBJECTS OF THE CONTROL SYSTEM IS A TONE-FREQUENCY SIGNAL - Dombrovskiy, Zbishek (International Journal of Computing, 2014)
Application of tone signals from limited range low frequencies (LF) band is an effective mean for energy consumption systems (СS) objects identification under their control above radio channels networks. With purpose for determination of requirements to characteristics of digital tone signals processing a method of evaluation of maximum quantity of confidence-identified of СS objects in the network with a radio channel is offered. On the foundation of had been determined requirements for the construction of digital devices of generation and filtration of tone signals is compatible with authentication of СS objects the appropriate structure is offered and its confidence is explored. Graphics of dependences of probability identification of the objects vs. signal to noise ratio at the different fault probability are presented and results of their comparing analyses are given.